Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Justify the first step that David took in verifying that x = 5 is a solution for the equation
8x – 13 = 2x + 17.

8x – 13 = 2x + 17
8(5) – 13 = 2(5) + 17
A.
David multiplied 8 by 5.
B.
David subtracted 13 from both sides.
C.
David replaced x with 5.
D.
David added 17 to both sides.


Sagot :

Answer:

Step by step I don't see the correct first step.

Step-by-step explanation:

Solve for x:

8 x - 13 = 2 x + 17

Hint: | Move terms with x to the left hand side.

Subtract 2 x from both sides:

(8 x - 2 x) - 13 = (2 x - 2 x) + 17

Hint: | Combine like terms in 8 x - 2 x.

8 x - 2 x = 6 x:

6 x - 13 = (2 x - 2 x) + 17

Hint: | Look for the difference of two identical terms.

2 x - 2 x = 0:

6 x - 13 = 17

Hint: | Isolate terms with x to the left hand side.

Add 13 to both sides:

6 x + (13 - 13) = 13 + 17

Hint: | Look for the difference of two identical terms.

13 - 13 = 0:

6 x = 17 + 13

Hint: | Evaluate 17 + 13.

17 + 13 = 30:

6 x = 30

Hint: | Divide both sides by a constant to simplify the equation.

Divide both sides of 6 x = 30 by 6:

(6 x)/6 = 30/6

Hint: | Any nonzero number divided by itself is one.

6/6 = 1:

x = 30/6

Hint: | Reduce 30/6 to lowest terms. Start by finding the GCD of 30 and 6.

The gcd of 30 and 6 is 6, so 30/6 = (6×5)/(6×1) = 6/6×5 = 5:

Answer: x = 5

We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.